A thermally aware performance analysis of quantum cellular automata logic gates - Sujatha Kotte; Ganapavarapu Kanaka Durga (Institute of Advanced Engineering and Science, 2023)
The high-performance digital circuits can be constructed at high operating frequency, reduced power dissipation, portability, and large density. Using conventional complementary-metal-oxide-semiconductor (CMOS) design process, it is quite difficult to achieve ultra-high-speed circuits due to scaling problems. Recently quantum dot cellular automata (QCA) are prosed to develop logic circuits at atomic level. In this paper, we analyzed the performance of QCA circuits under different temperature effects and observed that polarization of the cells is highly sensitive to temperature. In case of the 3-input majority gate the cell polarization drops to 50% with an increase in the temperature of 18 K and for 5 input majority gate the cell polarization drops more quickly than the 3-input majority. Further, the performance of majority gates also compared in terms of area and power dissipation. It has been noticed that the proposed logic gates can also be used for developing simple and complex and memory circuits.